Crystallization kinetics of Ni51Mn36Sn13 free-standing alloy thin films. (August 2016) - Wang, Z.H.; Guo, E.J.; Tan, C.L.; Tian, X.H.
Abstract: The crystallization kinetics of the Ni51 Mn36 Sn13 free-standing alloy thin films is investigated by differential scanning calorimetry (DSC) in the mode of non-isothermal and isothermal annealing. The DSC curves have been analyzed in terms of activation energy and kinetic model. It is found that all the DSC curves have a single exothermic peak which is asymmetrical, with a leading edge and a long high temperature tail. The activation energy from an amorphous state to crystallization of Ni51 Mn36 Sn13 free-standing alloy thin films is found to be 59 kJ/mol by Avrami's method and 54 kJ/mol by Kissinger's method. The DSC curves fitting procedure reveals that the crystallization of Ni51 Mn36 Sn13 free-standing alloy thin films follows the JMA-like kinetic model with the Avrami exponent varying from 1.17 to 1.73 under different temperatures, which indicates diffusion-controlled growth with the crystallization temperature. Highlights: Crystallization kinetics of the Ni51 Mn36 Sn13 free-standing alloy thin films are studied. The amorphous Ni51 Mn36 Sn13 free-standing thin film has low crystallization temperature and activation energy. The thin film is governed by diffusion-controlled two-dimensional growth of particles nucleated at constant rate.